HMG-CoA Lyase Deficiency: A Retrospective Study of 62 Saudi Patients - Alfadhel, Majid; Abadel, Basma; Almaghthawi, Hind; Umair, Muhammad; Rahbeeni, Zuhair; Faqeih, Eissa; Almannai, Mohammed; Alasmari, Ali; Saleh, Mohammed; Eyaid, Wafaa; Alfares, Ahmed; Al Mutairi, Fuad (Frontiers in Genetics, 2022)
3-Hydroxy-3-methylglutaryl-coenzyme A lyase deficiency (HMG-CoA lyase) is a rare inborn error of leucine degradation and ketone body synthesis, caused by homozygous or compound heterozygous disease-causing variants in HMGCL. In order to understand the natural history of this disease, we reviewed the biochemical, clinical, and molecular data for 62 patients from 54 different families with confirmed HMG-CoA lyase deficiency (HMGCLD) diagnosis from Saudi Arabia. The majority of the affected individuals were symptomatic. 38 patients (61.29%) presented with hypoglycemia at initial diagnosis, 49 patients (79.03%) developed metabolic acidosis. In 27 patients (43.54%), the disorder manifested at the neonatal period, mostly within the first days of life, while 35 (56.45%) patients were diagnosed within the first year of life or beyond. All the patients were alive and developed long-term neurological complications during data collection, which may significantly influence their quality of life. Common neurological findings include seizures 17/62 (27.41%), hypotonic 3/62 (4.83%), speech delay 7/62 (11.29%), hyperactivity 4/62 (4.83%), developmental delay 6/62 (9.677%), learning disability 15/62 (24.14%) and ataxic gate 1/62 (1.612%). MRI brain exhibited nonspecific periventricular and deep white matter hyperintense signal changes in 16 patients (25.80%), and cerebral atrophy was found in one (1/62; 1.612%) patient. We identified a founder variant (c.122G>A; p.Arg41Gln) in 48 affected individuals (77.41%) in the HMGCL gene. This is the largest cohort of HMGCLD patients reported from Saudi Arabia, signifying this disorder as a likely life-threatening disease, with a high prevalence in the region. Our findings suggest that diagnosis at an early stage with careful dietary management may avoid metabolic crises.